Sherris & Ryan's medical microbiology - Ryan, Kenneth J. (Kenneth James), 1940- (New York : McGraw Hill, 2022)
"In Sherris & Ryan's Medical Microbiology, the emphasis is on the text narrative, which is designed to be read comprehensively, not as a reference work. Considerable effort has been made to supplement this text with other learning aids such as the above-mentioned cases and questions as well as tables, photographs, and illustrations. This book is intended to be the primary text for students of medicine and medical science who are encountering microbiology and infectious diseases for the first time. Part I opens with a chapter that explains the nature of infection and the infectious agents at the level of a general reader. The following four chapters give more detail on the immunologic, diagnostic, and epidemiologic nature of infection with minimal detail about the agents themselves. Parts II through V form the core of the text with chapters on the major viral, bacterial, fungal, and parasitic diseases, and each begins with its own chapters on basic biology, pathogenesis, and antimicrobial agents"--
Part I. Infection / L. Barth Reller, Megan E. Reller, Kenneth J. Ryan, and Gayatri Vedantam -- Part II. Pathogenic viruses / Nafess Ahmad and W. Lawrence Drew -- Part III. Pathogenic bacteria / Paul Pottinger, L. Barth Reller, Kenneth J. Ryan, Gayatri Vedantam and Scott Weissman -- Part IV. Pathogenic fungi / J. Andrew Alspaugh and Julie M. Steinbrink -- Part V. Pathogenic parasites / Paul Pottinger and Charles R. Sterling.
Preceded by Sherris medical microbiology / editor, Kenneth J. Ryan. Seventh edition. 2018.
BIBINDX
Keywords: Communicable Diseases; Microbiology